Enhancing Islamic Religious Education Effectiveness in Private Vocational High Schools - Ahmad Baihaki; Andi Hermawan (Journal of Pedagogy and Education Science, 2026)
Education is a planned process that is essential for exploiting the potential of students, including those in Islamic Religious Education (IRE). However, IRE teaching Effectiveness in the private vocational high schools in Bogor Regency is not ideal. The study will examine the connection between transformational leadership, cooperative models of learning, and learning motivation on the Effectiveness of teaching IRE, and to make strategic recommendations that can be applied in learning institutions. A quantitative research approach was employed, and the sample size consisted of a proportionate number of participants, totaling 168. Data were analyzed through the path analysis and also through the SITOREM (Scientific Identification Theory to Conduct Operation Research on Education Management). The outcomes demonstrate that transformational leadership and the cooperative learning model have a strong and significant direct correlation with instructional Effectiveness. Additionally, learning motivation is a mediating variable that strengthens the relationship between these variables and the increase in instructional Effectiveness. The other need that the research has identified is the necessity to enhance various indicators of progress, research conditions, and achievement to maximize instructional outcomes. The findings of this study recommend that educational institutions should increase the application of transformational leadership practices, adopt cooperative learning more frequently, and introduce strategies to enhance student learning motivation as an instrument to increase the IRE as a whole in a vocational high school.